Mast Cell Tryptase Potentiates Neutrophil Extracellular Trap Formation - Gunnar Pejler; Sultan Alanazi; Mirjana Grujic; Jeremy Adler; Anna-Karin Olsson; Christian P. Sommerhoff; Fabio Rabelo Melo (Karger Publishers, 2021)
Previous research has indicated an intimate functional communication between mast cells (MCs) and neutrophils during inflammatory conditions, but the nature of such communication is not fully understood. Activated neutrophils are known to release DNA-containing extracellular traps (neutrophil extracellular traps [NETs]) and, based on the known ability of tryptase to interact with negatively charged polymers, we here hypothesized that tryptase might interact with NET-contained DNA and thereby regulate NET formation. In support of this, we showed that tryptase markedly enhances NET formation in phorbol myristate acetate-activated human neutrophils. Moreover, tryptase was found to bind vividly to the NETs, to cause proteolysis of core histones and to cause a reduction in the levels of citrullinated histone-3. Secretome analysis revealed that tryptase caused increased release of numerous neutrophil granule compounds, including gelatinase, lactoferrin, and myeloperoxidase. We also show that DNA can induce the tetrameric, active organization of tryptase, suggesting that NET-contained DNA can maintain tryptase activity in the extracellular milieu. In line with such a scenario, DNA-stabilized tryptase was shown to efficiently degrade numerous pro-inflammatory compounds. Finally, we showed that tryptase is associated with NET formation in vivo in a melanoma setting and that NET formation in vivo is attenuated in mice lacking tryptase expression. Altogether, these findings reveal that NET formation can be regulated by MC tryptase, thus introducing a novel mechanism of communication between MCs and neutrophils.